2019
DOI: 10.1111/psyg.12402
|View full text |Cite|
|
Sign up to set email alerts
|

The prevalence and clinical risk factors of insomnia in the Chinese elderly based on comprehensive geriatric assessment in Chongqing population

Abstract: Background Insomnia is a major public health problem affecting older people. This study aimed to investigate the prevalence and clinical risk factors of insomnia in a representative sample of Chinese elderly (≥ 60 years) in Chongqing. Methods A cross‐sectional study based on comprehensive geriatric assessment was conducted from January 2013 to February 2014. A questionnaire on sleep status was provided to each patient and insomnia was assessed according to the Diagnostic and Statistical Manual of Mental Disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
12
0
2
Order By: Relevance
“…Second, being separated from their children or partners can cause older people to become depressed and isolated and to lack emotional comfort (54,55). Finally, may problems can occur with aging, [e.g., cognitive decline, sleep disturbances, and malnutrition (56)]. Previous studies have reported that hypertension and diabetes are characterized by a long course, a poor prognosis, and are difficult to cure.…”
Section: Discussionmentioning
confidence: 99%
“…Second, being separated from their children or partners can cause older people to become depressed and isolated and to lack emotional comfort (54,55). Finally, may problems can occur with aging, [e.g., cognitive decline, sleep disturbances, and malnutrition (56)]. Previous studies have reported that hypertension and diabetes are characterized by a long course, a poor prognosis, and are difficult to cure.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the prevalence reported in most previous works, the insomnia prevalence revealed in this study is much higher. The prevalence was reported range 11.9-37.75% among the general population, community residents, adults, and the elderly in China [6,7]. Meanwhile, it was also higher than 24% reported for U.S. workers [9], 32.9% for Korean workers [10], and 4.7% for male workers in Japan [29], but similar to 39.7% for gas transmission industry workers in Iran [30].…”
Section: Discussionmentioning
confidence: 93%
“…However, the prevalence of insomnia and its associated factors are rarely known in steel workers, especially in China. Several socio-demographic, psychological, lifestyle-and be havior-related, as well as occupational factors are associated with insomnia, including anxiety, physical health, religious beliefs [5], sex [6], alcohol consumption [20], a lack of steady income, less frequent social contacts, reduced social capital, living alone [7], shift work [21], occupational stress [8], etc. However, little is known about whether the prevalence of insomnia and its associated factors are different across job categories of steel workers.…”
Section: Questionnaire Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The American Insomnia Survey, an epidemiological survey, showed that insomnia in the general population reached 22.1% based on the Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV-TR (2). The prevalence of insomnia increases with age, and its prevalence in the elderly is known to be around 20-55% (1,3,4). Chronic insomnia constitutes a vicious cycle that makes the disease more susceptible to fixation.…”
Section: Introductionmentioning
confidence: 99%